Impact of vulvovaginal atrophy of menopause: prevalence and symptoms in Italian women according to the EVES study. (4th May 2019) - Nappi, R. E.; Seracchioli, R.; Salvatore, S.; Cagnacci, A.; Di Paolantonio, T.; Busacca, M.; ,
Abstract: This cross-sectional study included postmenopausal women, aged 45–75 years, with the aim to assess the presence of vulvovaginal atrophy (VVA) confirmed by a clinical assessment in the Italian population attending menopausal/gynecological centers. Apart from baseline variables, women scored vaginal, vulvar and urinary VVA symptoms. Impact of VVA on sexual function and quality of life (QoL) was assessed thorough EuroQoL questionnaire (EQ5D3L), Day-to-Day Impact of Vaginal Aging (DIVA), Female Sexual Function Index (FSFI) and Female Sexual Distress Scale-revised (FSDS-R). A physical examination was carried out in accordance with routine gynecological practice. VVA was confirmed in 90% of the 1226 evaluable patients (aged 59.0 ± 7.3 years). The prevalence of postmenopausal women with VVA confirmed by gynecological clinical assessment was 75.3%. The patients with VVA confirmed ( n  = 926) had more severe symptoms ( p  < .0005), lower QoL (EQ-visual analog scale, p  = .008 and DIVA, p  < .0005) and worsened sexual function (FSFI and FSDS-R, p  < .0005 for both) when compared with the patients having nonconfirmed VVA ( n  = 140). VVA is highly prevalent among postmenopausal Italian women. The objective of VVA confirmation is associated with severe symptoms and impaired QoL and sexual function. A proactive approach of Italian clinicians to promote regular and early gynecological evaluation should be performed in order to delay the advancing of the disorder.